A Brinquedoteca Universitária da Universidade Federal do Pará, Campus Altamira como espaço de inclusão social de crianças com deficiência - COSTA, Thaina Neves da (2023)
This article aimed to understand the importance of the space of the University Toy Library for the development of the learning process of children with disabilities. The methodological approach was qualitative, in the form of field research. The investigation began with the question: What actions in the university toy library allow for the social inclusion of children with disabilities? The methodological instruments of the research were: notes in the field diary, photographic resources and participant observation. The research site was the University Toy Library of the Faculty of Education, Campus of Altamira-PA. The University Toy Library enables the social inclusion of children with disabilities due to the importance of space, because through play, the child develops and, in a playful way, enhances the development of skills and the teaching and learning process.